2004
DOI: 10.1310/rrx7-49me-27v7-mwwv
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Characterization of Different Dose Combinations of Coadministered Tipranavir and Ritonavir in Healthy Volunteers

Abstract: This phase 1 study demonstrated that RTV-boosted TPV achieves concentrations that are expected to be effective in treating drug-experienced patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
31
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 15 publications
5
31
1
Order By: Relevance
“…Ritonavir is a protease inhibitor clinically used as an anti-HIV drug. It also widely used as a CYP3A4 inhibitor to boost the effect of other anti-HIV agents for the treatment of AIDS [23] . Some research has indicated that the elevation and prolongation of the plasma levels of some protease inhibitors (such as tipranavir, saquinavir or indinavir) by ritonavir coadministration may produce a composite suppression of HIV viral replication in excess of the sum of that was observed with either agent individually [24,25] .…”
Section: Discussionmentioning
confidence: 99%
“…Ritonavir is a protease inhibitor clinically used as an anti-HIV drug. It also widely used as a CYP3A4 inhibitor to boost the effect of other anti-HIV agents for the treatment of AIDS [23] . Some research has indicated that the elevation and prolongation of the plasma levels of some protease inhibitors (such as tipranavir, saquinavir or indinavir) by ritonavir coadministration may produce a composite suppression of HIV viral replication in excess of the sum of that was observed with either agent individually [24,25] .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro data have shown that resistance to TPV develops slowly (5). When TPV is coadministered with ritonavir (RTV) as a booster, TPV has been shown to have potent antiviral activity in multidrug-experienced patients (3,6,9,12). In the RESIST-1 and the RESIST-2 studies, the efficacy and safety of TPV-RTV (500 mg/200 mg twice daily) in 1,509 highly treatment-experienced HIV-1-positive patients were assessed.…”
mentioning
confidence: 99%
“…In clinical studies with healthy volunteers and HIV-infected patients, TPV pharmacokinetic parameters, including the steady-state trough concentration, the area under the concentration-time curve (AUC) for plasma, the maximum concentration in plasma during the steady state (C max ), and the apparent terminal half-life (t 1/2 ), were substantially improved with the concomitant administration of ritonavir (RTV) (8,9). Since RTV strongly inhibits cytochrome P450 3A4 (CYP3A4) (5), the boosted levels of TPV in plasma with the coadministration of TPV and RTV (TPV/r) indicate that the metabolism of TPV occurs via the cytochrome P450 (CYP450) pathway (8,9).…”
mentioning
confidence: 99%
“…Since RTV strongly inhibits cytochrome P450 3A4 (CYP3A4) (5), the boosted levels of TPV in plasma with the coadministration of TPV and RTV (TPV/r) indicate that the metabolism of TPV occurs via the cytochrome P450 (CYP450) pathway (8,9). Phase II studies have also demonstrated that TPV is an inducer of CYP450 metabolism or intestinal P glycoprotein efflux, thereby lowering systemic RTV concentrations when administered with RTV (8,11,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation